Child Anxiety Prevention Study: Impact on Functional Outcomes - Pella, Jeffrey (Child Psychiatry Hum Dev, 2017)
This study examined the impact of a selective anxiety prevention program for offspring of clinically anxious parents on three domains of child functioning: 1) social, 2) familial, and 3) emotional/behavioral. Dyads were randomized into either the Coping and Promoting Strength program (CAPS; n=70) or Information Monitoring (IM; n=66) comparison group. Multi-informant assessments were conducted at baseline, post intervention, and 6 and 12 months follow-ups. Random effects mixed models under the linear growth modeling (LGM) framework was used to assess the impact of CAPS on growth trajectories. Over time, children in the CAPS group had significantly lower anxiety, anxious/depressed symptoms, and lower total behavior problems (parent report), compared to children in IM group. The intervention did not impact other domains assessed (e.g., social functioning), which may be due to “floor effects” on these measures. Longitudinal follow-up data is needed to provide valuable information about this high risk population.